The Effect Of The DoseOfNitrogen Fertilizer To The Growth And Yield OfMustard Greens On Alluvial - Sari, Jaka Purnama; Mustamir, Elly; Santoso, Eddy (Jurnal Sains Mahasiswa Pertanian, 2019)
The aim of this research is to find out the bestdoseof nitrogen fertilizerfor the growth and yield of mustard greens on alluvial soil. The research was conducted from 04 mayto 04juni 2019 in the experimental garden of the Faculty of Agriculture, Tanjungpura University, Pontianak. The study used a completely randomized design (CRD) method in which the application of organic fertilizer as a single factor. The treament were designed in five level ofÂ  concentration and 5 treatments with 5 replications and each replication consisted of 4 sample plants. The treatment in question is p1 = Urea 150 kg/ha,p2 = Urea 175 kg/ha, p3 = Urea 200 kg/ha,p4 = Urea 225 kg/ha and p5 = Urea 250 kg/ha. Variabeles observed in research wereroot volume (cm3), the number of spad unit(spad unit), leaf area (cm2), the dry weight of the plant (g), and the fresh weight of the plant (g). The results showed that the using of urea fertilizer with dose 250 kg/ha is best results providefor the growth and yield of mustard greens on alluvial.Keywords:alluvial, nitrogen fertilizer, mustardgreens